Acetylcholine Promotes Binding of α-Conotoxin MII for α(3)β(2) Nicotinic Acetylcholine Receptors - Sambasivarao, Somisetti V. (2014)
α-Conotoxin MII (α-CTxMII) is a 16 amino acid peptide with the sequence GCCSNPVCHLEHSNLC containing disulfide bonds between Cys2-Cys8 and Cys3-Cys16. This peptide, isolated from the venom of the marine cone snail Conus magus, is a potent and selective antagonist of neuronal nicotinic acetylcholine receptors (nAChRs). To evaluate the impact of channel-ligand interactions on ligand binding affinity, homology models of the heteropentameric α(3)β(2)-nAChR were constructed. The models were created in MODELLER using crystal structures of the Torpedo marmorata-nAChR (Tm-nAChR, PDB ID: 2BG9) and the Aplysia californica-acetylcholine binding protein (Ac-AChBP, PDB ID: 2BR8) as templates for the α(3) and β(2) subunit isoforms derived from rat neuronal nAChR primary amino acid sequences. Molecular docking calculations were performed with AutoDock to evaluate interactions of the heteropentameric nAChR homology models with the ligands acetylcholine (ACh) and α-CTxMII. The nAChR homology models described here bind ACh with commensurate binding energies to previously reported systems, and identify critical interactions that facilitate both ACh and α-CTxMII ligand binding. The docking calculations revealed an increased binding affinity of the α(3)β(2)-nAChR for α-CTxMII with ACh bound to the receptor, which was confirmed through two-electrode voltage clamp experiments on oocytes from Xenopus laevis. These findings provide insights into the inhibition and mechanism of electrostatically driven antagonist properties of the α-CTxMIIs on nAChRs.